Integration of GeoGebra and Maple in the construction of mathematical competences in civil engineering students in a private university, Cajamarca - Cenas Chacón, Fernando Ysmael; Ramírez Sobalvarro, Yasmina; Gamboa Ferrer, Leydidiana Rosibel; Blaz Fernandez, Fanny Evelyn (LACCEI, 2024)
It is the presence of technology and its integration in the classroom that generates important effects on mathematics learning. In this sense, the purpose of this study was to determine the integration of GeoGebra and Maple softwares and its influence on the improvement of mathematical competences. For this purpose, a quantitative study with a quasi-experimental design was carried out with a sample of 80 students in the experimental group and 80 in the control group, both of them civil engineering students of a private university in Cajamarca in the 2023-II cycle. For the collection of information, the methodology of the inverted classroom was used and as instruments the tests applied by means of the continuous evaluation, during 14 weeks, reflecting as a result in the global mathematical competence in the pre-test at 75% in the high level, This situation improved significantly in the post-test when 96% of the participants reached this same level and when compared to the control group, in the post-test, 52% was achieved, this indicated an evident improvement and was confirmed when contrasting the hypothesis using the Kolmogorov-Smirnov Z test for independent samples, resulting in a statistical significance of 0. 009, and the Z value was 1.650, which led to its acceptance. It was then concluded that GeoGebra and Maple play a valuable role in the process of improving mathematical competencies.